Hubungan Kompensasi Dengan Kepuasan Kerja Guru Pendidik Khusus (GPK) Sekolah Dasar Inklusif Di Kota Padang - Harri Kurniawan; Devi Agustianti (Psyche 165 Journal, 2019)
This research was conducted on Special Educator Teachers (GPK) Inclusive Primary Schools in Padang City. The purpose of this study was to determine the relationship between compensation and job satisfaction of Teachers of Special Educators (GPK) Inclusive Primary Schools in the City of Padang. The sample selection technique in this study uses Sampling Random Sampling,random sampling which is atechnique regardless of the strata that exist in that population (Sugiyono, 2014). The sample in this study amounted to 78 people. Test the validity and reliability using Cronbach Alpha.The trial results show the validity coefficient in the scale of compensation from 0.309 to 0.811 while the reliability coefficient is 0.941. The results of the coefficient trial of the validity of the job satisfaction scale show from 0.301 to 0.755 with a reliability coefficient of 0.917. Hypothesis test results show the magnitude of the correlation coefficient of 0.835 with a significant level p = 0,000. It means that it can be concluded that there is a significant relationship between compensation and job satisfaction. Positive values indicate that the higher the compensation, the better the teacher's job satisfaction, and vice versa the lower the compensation, the worse the job satisfaction of the Special Educator Teacher (GPK). The effective contribution of the compensation variable to job satisfaction is 70%.